Sensibilization Spectrum in Preschool Children with Atopic Dermatitis - Tat'yana S. Kashinskaya; Natal'ya V. Shahova; Yurij F. Lobanov; Natal'ya K. Bishevskaya (Педиатрическая фармакология)
Background. Atopic dermatitis (AD) is an allergodermathosis that is widespread in children and adult populations. Sensibilization to food allergens prevails in children of early age, and to airborne allergens in older age. Impairments of skin barrier lead to increase in Staphylococcus aureus colonization and finally aggravate the course of AD and the sensibilization level.Objective. The aim of the study is to estimate the sensibilization spectrum in 3-6 years old children with AD and its correlation with severity.Methods. It was cross sectional study with two independent cohorts of 3-6 years old children with and without (healthy) AD. Estimation of sensibilization spectrum and revealing of correlation with disease severity were performed.Results. The study includes 106 children aged 4.4 ± 1.2 year (58.5% boys and 41.5% girls). Polysensibilization was revealed in 28.3% of children. According to our data: 3-6 years old children with AD most often had sensibilization to the cat epithelium (34.9%), cow's milk proteins (22.6%), Dermatophagoides pteronyssinus mite (16.0%). Sensibilization to enterotoxins of Staphylococcus aureus was revealed in 7.5% children. We have recorded weak positive correlation between the AD severity and the level of specific IgE to airborne and food allergens. There was no statistically significant correlation between the AD severity and the level of specific IgE to Staphylococcus aureus enterotoxins A and B. Conclusion. The most common sensibilization type among 3-6 years old children with AD was one to airborne allergens. Sensibilization to the cat epithelium prevails among airborne allergens, to the cow's milk proteins — among food allergens. The weak positive correlation between the AD severity and the level of specific IgE to airborne and food allergens was revealed. The weak negative correlation with the level of specific IgE to Staphylococcus aureus enterotoxins A and B was revealed, thus the data was statistically insignificant.